Understanding the gap between knowledge and practice of handwashing in rural India: evidence from a cross-sectional study. (7th November 2022) - Chatterjee, Sayantani; Roy, Manabendra Nath; Banerjee, Koushiki; Mojumdar, Sujoy; Osbert, Nicolas
Abstract: Limited studies in India had captured the gap in knowledge and practice of handwashing in the community. This study assesses the gap in knowledge and practice of handwashing in rural India. The study was conducted across 10 districts in five states of India – Andhra Pradesh, Assam, Maharashtra, Odisha and West Bengal from December 2021 to January 2022 by the SIGMA Foundation, Kolkata in collaboration with UNICEF India. Descriptive statistics, bivariate analysis, creation of indices and multinomial logistic regression were employed. Findings demonstrated that both knowledge of different aspects of hand hygiene and practice of handwashing with soap and water (HWWS) at critical times varied by socio-economic groups and also across the districts/states. Half of the respondents used only water to wash their hands after taking meals, before serving food, whenever their hands seemed dirty and before eating or cooking. Overall, the 'HWWS knowledge index' was 0.46, whereas the 'HWWS practice index' was 0.36. The correlation coefficient between the two was 0.36. The HWWS practice index was lower than the HWWS knowledge index for 50% of the sampled households. Both HWWS knowledge and practice indices were higher among females, higher educated and younger population. The gap between handwashing practice and knowledge was also higher among females and higher educated. HIGHLIGHTS: First multi-state study in rural India aimed at understanding the gap between knowledge and handwashing practice after COVID-19. Knowledge and practice of handwashing with soap and water at critical times are inadequate. Substantial gap in knowledge and practice of handwashing with soap and water exists by socio-economic status and by districts. Graphical Abstract